Validitas Permainan Ular Tangga Kimia Sebagai Media Pembelajaran Pada Materi Asam Basa Kelas XI SMA atau MA - Amalia Putri Lubis; Iswendi Iswendi (Edukimia, 2021)
The chemical ladder snake game is one of the variations in learning media in doing practice questions. This type of research is Research and Development (R and D) using the 4-D model which includes the stages of define, design, develop, and disseminate. The research is limited to the develop part of the validity test. The instrument used was a validity questionnaire given to two UNP chemistry lecturers and two chemistry teachers at SMA N 3 Padang. Data collection techniques were analysed using Aiken V formula. Data analysis showed that the level validity of the chemical ladder snake was 0,75, so it can be concluded that the chemical ladder snake developed was valid as a learning media for the acid-base material of class XI SMA or MA.